Novel CDKs inhibitors for the treatment of solid tumour by simultaneously regulating the cell cycle and transcription control. (1st January 2020) - Wang, Xin; Deng, Kaiyuan; Wang, Cheng; Li, Yao; Wang, Tianqi; Huang, Zhi; Ma, Yakun; Sun, Peiqing; Shi, Yi; Yang, Shengyong; Fan, Yan; Xiang, Rong
Abstract: A novel series of cyclin-dependent kinases (CDKs) inhibitors, which play critical roles in the cell cycle control and regulation of cell transcription, were synthesised. A systematic study of enzymatic and cellular assays led to the identification of compound X22 with a nanomolar potency against CDK4 and CDK9 and potent antiproliferative activities against a panel of tumour cell lines. X22 could induce cell cycle arrest and cell apoptosis in cancer cell lines. X22 dose-dependently inhibits signalling pathways downstream of CDKs in cancer cells. In vivo antitumor activity assays, oral administration of X22 led to significant tumour regression in mouse model without obvious toxicity. Superior anti-cancer efficacy in vitro and in vivo of X22 demonstrated combined depletion of cell cycle and transcriptional CDK all contributed to antitumor activity. Taken together, concomitant inhibition of cell cycle and transcriptional CDK activities provided valuable guide for further structural optimisation.